Psychologiczne aspekty przekazu reklamowego - Morokiszka, Marta (My University, 2011)
Niniejsza praca opisuje związki reklamy z psychologią. Przedstawiono w niej czynniki oraz mechanizmy jakie przekaz reklamowy czerpie z tej dziedziny nauki, by jeszcze skuteczniej oddziaływać na człowieka i wpływać na jego decyzje zakupowe. Badania własne dotyczące wiadomości wpływu komunikatu reklamowego na postępowanie konsumenta (wybory zakupowe), przeprowadzono na 50-ciu przypadkowo wybranych respondentach w dniach od 24 do 27 maja 2010 roku, przed hipermarketem Real oraz Galerią Sandecja w Nowym Sączu. W badaniach wykorzystano najpopularniejsze narzędzie badawcze jakim jest ankieta. Analiza badań pozwoliła na wysunięcie następujących wniosków: -znaczna większość ankietowanych twierdzi, że nie jest podatna na reklamę i jej chwyty, i nie ulega jej wpływowi przy wyborze produktów/usług, -respondenci uznali reklamę jako rzecz dobrą i lubianą, -duża liczba badanych nie wie, iż reklama jest powiązana z psychologią i nie zna czynników, z których korzysta, by mamić i przyciągać nabywców, -najskuteczniej uwagę badanych przyciąga w przekazie reklamowym dźwięk, kolor oraz pomysł, -za najbardziej skuteczną i zachęcającą do zakupu, ankietowani uznali reklamę telewizyjną. Wnikliwa analiza zebranych materiałów pozwoliła na potwierdzenie wszystkich hipotez postawionych w niniejszej pracy do weryfikacji.

My Bachelor’s Degree dissertation deals with the relationship between advertisement and psychology. It depicts some factors and actions which advertising message derives from that field of knowledge with the aim of which affecting a man and to have effect on his purchase decision. My own research concerning an awareness of the advertising message influence on consumer conduct (purchase selection) has been carried out in front of a hypermarket Real and a Sandecja Gallery in Nowy Sącz on fifty randomly selected respondents, from 24 to 27 may 2010 year. In my research, the most popular research tool, a survey was used. My own exploration allowed to propose following conclusions: - the vast majority of respondents hold that they are not prone to advertisements, stunts that advertising agencies makes, and that they are not succumb to the advertisement impact , when choosing products/services, -advertisement was acknowledged as positive and liked by respondents, -large number of respondents don’t know that advertisement is linked with psychology. Moreover, they are not familiar with factors, which are used by advertisement in order to beguile and attract purchaser, -sound, in the opinion of respondents, is the most effective means in the advertising message to draw their attention, -respondents have adjudged television commercials as the most effective and encouraging to (do the) shopping. An Analysis of collected materials does ascertain all the hypothesis that I have made in my Bachelor’s Degree dissertation to your verification.
Psychological aspects of advertising message
Keywords: reklama; psychologia reklamy; mechanizmy psychologiczne; decyzje zakupowe; ankieta; advertisement; the psychology of advertising; psychological mechanisms; purchase selections; survey